2018
DOI: 10.2147/copd.s144108
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of blood eosinophil levels in a Japanese COPD clinical trial database and in the rest of the world

Abstract: BackgroundBlood eosinophil measurements may help to guide physicians on the use of inhaled corticosteroids (ICS) for patients with chronic obstructive pulmonary disease (COPD). Emerging data suggest that COPD patients with higher blood eosinophil counts may be at higher risk of exacerbations and more likely to benefit from combined ICS/long-acting beta2-agonist (LABA) treatment than therapy with a LABA alone. This analysis describes the distribution of blood eosinophil count at baseline in Japanese COPD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We searched 192 studies, of which nineteen studies (7)(8)(9)(10)(11)(12)(13)(14)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) with 40,112 participants were included in the final analysis (Figure 1). According to the cut-off level of 2% eosinophil in the blood, 22,043 and 18,069 patients were classified as having eosinophilic and non-eosinophilic COPD, respectively.…”
Section: Study Descriptionmentioning
confidence: 99%
“…We searched 192 studies, of which nineteen studies (7)(8)(9)(10)(11)(12)(13)(14)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) with 40,112 participants were included in the final analysis (Figure 1). According to the cut-off level of 2% eosinophil in the blood, 22,043 and 18,069 patients were classified as having eosinophilic and non-eosinophilic COPD, respectively.…”
Section: Study Descriptionmentioning
confidence: 99%
“…Indeed, in the most recent guidelines, GOLD recommends ICS explicitly in patients with high (>300 cells/mm 3 ) eosinophil counts, which is present in +/-20% of the COPD population. 1,40,41 Yet, to also account for other risk groups where ICS may be beneficial (e.g. frequent exacerbators, asthma-overlap.…”
Section: Intervention MIXmentioning
confidence: 99%
“…frequent exacerbators, asthma-overlap. 1,[40][41][42][43][44][45] ), we considered a slightly higher percentage of ICS (i.e. 25%) in the new treatment mix.…”
Section: Intervention MIXmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 5th version of the Japanese guidelines published by The Japanese Respiratory Society in 2018, the description reads that ICS should be given only in patients with asthma-complicated COPD or Asthma and COPD Overlap (ACO) [12]. It is reported that the blood eosinophil data from global studies are of relevance in Japan although there was a slightly lower median eosinophil count for Japanese patients within multi-country studies [13]. One of the opposing views is that BEC may be liable to variation and considered to be unreliable as a biomarker [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%